2016
DOI: 10.1002/clc.22649
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dabigatran, rivaroxaban, and warfarin for stroke prevention in Chinese patients with atrial fibrillation: the Hong Kong Atrial Fibrillation Project

Abstract: Background Little is known about the comparative effectiveness and safety of non–vitamin K antagonist oral anticoagulants (NOAC) compared to warfarin in Chinese atrial fibrillation (AF) patients. Our aim was to compare the ischemic stroke risk reduction and incidence of intracranial hemorrhage (ICH) of warfarin in relation to quality of anticoagulation control (as reflected by time in therapeutic range [TTR]), and to dabigatran and rivaroxaban in a real‐world cohort of Chinese AF patients. Hypothesis NOAC, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 19 publications
(45 reference statements)
4
46
1
Order By: Relevance
“…Contrary, a Chinese study estimated a lower associated risk of ischaemic stroke for dabigatran 110 mg compared with rivaroxaban 15 mg and 20 mg . The American and Chinese studies were restricted to only compare rivaroxaban versus dabigatran, whereas a recently published American study by Noseworthy et al . compared dabigatran, rivaroxaban and apixaban in three one‐to‐one propensity‐score‐matched cohorts.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Contrary, a Chinese study estimated a lower associated risk of ischaemic stroke for dabigatran 110 mg compared with rivaroxaban 15 mg and 20 mg . The American and Chinese studies were restricted to only compare rivaroxaban versus dabigatran, whereas a recently published American study by Noseworthy et al . compared dabigatran, rivaroxaban and apixaban in three one‐to‐one propensity‐score‐matched cohorts.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to our results, the two American studies found no significant difference in associated stroke risk between rivaroxaban and dabigatran. Contrary, a Chinese study estimated a lower associated risk of ischaemic stroke for dabigatran 110 mg compared with rivaroxaban 15 mg and 20 mg . The American and Chinese studies were restricted to only compare rivaroxaban versus dabigatran, whereas a recently published American study by Noseworthy et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The J‐ROCKET AF trial (Japanese Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared With Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation) showed that the pharmacokinetic profiles of a 15‐mg dose of rivaroxaban in Japanese patients was similar to the 20‐mg dose in white patients, indicating that low‐dose rivaroxaban with 15/10 mg is adequate for stroke prevention in AF patients 35. Chan et al also reported that low‐dose dabigatran was associated with the lowest risk of ischemic stroke and ICH compared with warfarin with a variety of quality controls in elderly Chinese with AF 36, 37, 38. Further studies are warranted to determine the so‐called “optimal” dose of NOACs in Asians with AF.…”
Section: Discussionmentioning
confidence: 97%
“…35 Chan et al also reported that low-dose dabigatran was associated with the lowest risk of ischemic stroke and ICH compared with warfarin with a variety of quality controls in elderly Chinese with AF. [36][37][38] Further studies are warranted to determine the so-called "optimal" dose of NOACs in Asians with AF.…”
Section: Discussionmentioning
confidence: 99%